DIFFERENTIALLY EXPRESSED GENES AND THEIR SIGNIFICANCE THE SUBSTANTIA NIGRA OF MICE WITH 1-METHYL-4-PHENYL-1,2,3,6-TETRAHYDROPYRIDINE-INDUCED PARKINSON’S DISEASE - LI Beining, YAO Zhengyang, JIAO Qian, CHEN Xi, JIANG Hong, DU Xixun (精准医学杂志, 2023)
Objective To investigate the differentially expressed genes (DEGs) in the substantia nigra of mice with Parkinson’s disease (PD) induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) based on bioinformatics, as well as their role in the pathological and progression of PD. Methods GEO database was used to obtain the gene expression microarray data in the substantia nigra of mice in the normal group and the PD model group, and the bioinformatics method was used to screen for DEGs in the substantia nigra between the normal group and the PD model. Metascape tool was used to perform GO functional enrichment analysis and KEGG pathway enrichment analysis. Quantitative real-time PCR was used to measure the mRNA expression levels of key functional genes regulating neuronal apoptosis and prion transmission. Results There were 174 upregulated DEGs and 173 downregulated DEGs in the substantia nigra of mice with MPTP-induced PD (P<0.05, fold change >0.26). The upregulated genes were significantly enriched in the pathways regulating prion transmission, neuronal development, iron homeostasis, and export across the plasma membrane, while the downregulated genes were significantly enriched in the pathways regulating synaptic vesicle release, transsynaptic complex transmission, neuronal apoptosis, and actin in cytoskeleton. Compared with the normal group, the PD model group had significant reductions in the expressions of Bdnf and Fbxw7 in the substantia nigra of mice (t=2.25,2.39,P<0.05), while there was no significant difference in the expression of sod1 between the two groups (P>0.05). Conclusion There are significant changes in the key functional genes Bdnf and Fbxw7 that regulate neuronal apoptosis in PD model, which lays a foundation for further clarifying their role in the pathological progression of PD.